PENINGKATAN KEANDALAN PENYULANG TUKAD MUSI DENGAN PENAMBAHAN PENYULANG BATANGHARI DENGAN POLA LOOP - Rahmadi Kurniawan, Ian; Dyana Arjana, I Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i03.p14, 2023)
Reliability of the distribution system is one of the critical challenges and important indicators in the electricity power system. The indicators determining reliability are SAIFI (System Average Interruption Frequency Index) and SAIDI (System Average Interruption Duration Index). The method used to improve the reliability of the distribution system in this research is by converting two radial feeders, namely Tukad Musi feeder and Batanghari feeder, into a loop configuration.The calculation results show that before the improvement, the SAIDI value for the Tukad Musi feeder is 26.59 hours/customer/year, and the SAIFI is 1.92 interruptions/customer/year. The initial values of SAIDI for the Batanghari feeder are 18.14 hours/customer/year, and SAIFI is 1.69 interruptions/customer/year. By implementing a loop configuration through the addition of extra channels at both ends of the feeders, the SAIDI is reduced to 24.79 hours/customer/year, and SAIFI becomes 1.89 interruptions/customer/year. Further improvements are achieved by maneuvering a portion of the load, resulting in SAIDI of 21.51 hours/customer/year and SAIFI of 1.83 interruptions/customer/year.This study contributes to enhancing the reliability of the distribution system by converting radial feeders into loop configuration. The findings can serve as guidelines for planning and developing a more reliable and efficient distribution system.